Kesadahan Air Sumur Warga Desa Ligarmukti Kabupaten Bogor - Angki Purwanti; Tri Pasetyorini (Jurnal Kesehatan Cendikia Jenius, 2024)
Ligarmukti is a village in Bogor Regency which is crossed by limestone hills. The source of water consumed by village residents comes from dug wells which characterize hard water. The aim of the research was to determine the total hardness level of the well water of residents of Ligarmukti village RT/RW 12/06 Bogor Regency which is used for drinking and cooking purposes. The research design was descriptive observational with laboratory examination. As a sample, 29 well water was used taken from 29 wells dug by residents of RT/RW 12/06 Ligarmukti village, Bogor Regency, with a population of 35 wells. Determination of total hardness is carried out using complexometric titration. Water hardness is categorized based on the International of Drinking Water from WHO (2017) into "soft", "moderately hard", "hard" and "very hard".Of the 29 well water examined, 16 (55.2%) found "hard" water and 13 (44.8%) "very hard" well water. As many as 29 (100%) well water is not suitable for consumption.The minimum, maximum and average total hardness of well water is (206.78, 465.50 and 309.04) mg/L. Routine and prolonged consumption of drinking water with a hardness level of > 300 mg/L, which is included in the "very hard" water category, will affect kidney health. The well water of residents of Ligarmukti village RT/RW 12/06 Bogor Regency is not suitable for direct consumption. It is recommended for future researchers to soften water using a method that can be applied on a household scale. It is also recommended that the community service team from Poltekkes Jakarta III carry out calcium oxalate examinations in the urine of residents of the research area.